2017
DOI: 10.12998/wjcc.v5.i6.238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of double platinum agents, combination of miriplatintransarterial oily chemoembolization and cisplatinhepatic arterial infusion chemotherapy, in patients with hepatocellular carcinoma: Report of two cases

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers and the third highest cause of cancer-associated mortality worldwide. The treatment of HCC is complicated by its variable biological behavior and the frequent coexistence of chronic liver disease, particularly cirrhosis. To date, multiple treatment modalities have been developed according to the stage of the tumor and the hepatic functional reserve, including transarterial treatments such as transarterial chemoembolization, transarterial oily che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…From previous studies and our clinical practice, we found that the mechanisms by which HAIC affects HCCs might include the inhibition of angiogenesis, stimulation of immunity, and direct inhibition of tumor cell proliferation. 8 , 14 , 20 22 Inhibition of angiogenesis is the most important mechanism. During HAIC treatment, the angiogenesis of tumor cells can be inhibited by direct destruction and inhibition of proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies and our clinical practice, we found that the mechanisms by which HAIC affects HCCs might include the inhibition of angiogenesis, stimulation of immunity, and direct inhibition of tumor cell proliferation. 8 , 14 , 20 22 Inhibition of angiogenesis is the most important mechanism. During HAIC treatment, the angiogenesis of tumor cells can be inhibited by direct destruction and inhibition of proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity screening of RuC showed that HepG2 and HeLa cells were sensitive cell lines over 48 and 72 h of exposure (Table 1, Supplementary Table S2). In all of the experiments, the metallic chemotherapeutic drug cisplatin was used as a positive control because it has been used for the treatment of HCC [31,32] and cervical tumors [33,34]. After 48 h of drug exposure, RuC was cytotoxic in HepG2 and HeLa cells at nanomolar concentrations, whereas cisplatin had similar cytotoxicity in the micromolar range (Figure 2), thus indicating the higher in vitro potency of RuC against HepG2 and HeLa cells compared with cisplatin.…”
Section: Discussionmentioning
confidence: 99%